Q. 113.6( 150 Votes )

Sum of the

Answer :

Given: Sp = a, Sq = b, and Sr = c

To Prove:


Let a1 be the first terms and d be the common difference of the A.P.

We know that sum of n terms of an A.P is given by:

where, a = first term
n = nth terms 
d = common difference

Therefore, we have,

Sum of first p terms =


Sum of first q terms =


Sum of first p terms =


Subtracting (2) from (1)

Subtracting (3) from (2)

From (IV) and (V),

pq (p – q) (2br – 2cq) = qr (q – r) (2aq – 2bp)

p (p – q) (2br – 2cq) = r (q – r) (2aq – 2bp)

(aqr – bpr) (q – r) = (bpr – cpq) (p – q)

Dividing both sides by pqr

Hence, proved.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses

There are n A.M.sRD Sharma - Mathematics

If x, y, z are inRD Sharma - Mathematics

Insert 7 A.M.s beRD Sharma - Mathematics

The 10th</suRD Sharma - Mathematics

Insert five numbeRD Sharma - Mathematics

The 4th</supRD Sharma - Mathematics

Insert 4 A.M.s beRD Sharma - Mathematics

An A.P. consists RD Sharma - Mathematics

How many terms arRS Aggarwal - Mathematics

In a cricket tourMathematics - Exemplar